Calculati :75•{20+10•[3•(44÷11-7•0)+2]÷7-(145÷5+10÷1)}-12•6=
Utilizator anonim:
a lui cine este corect
Răspunsuri la întrebare
Răspuns de
2
75•{20+10•[3•(44÷11-7•0)+2]÷7-(145÷5+10÷1)}-12•6=
=75•{20+10•[3•(4-0)+2]÷7-(29+10)}-12•6=
=75•{20+10•[3•4+2]÷7-39}-12•6=
=75•{20+10•[12+2]÷7-39}-12•6=
=75•{20+10•14÷7-39}-12•6=
=75•{20+140÷7-39}-12•6=
=75•{20+20-39}-12•6=
=75•{40-39}-12•6=
=75•1-12•6=
=75-12•6=
=75-72=
=3
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă